Using Digital Natural History Collections in K-12 STEM Education. (1st October 2020) - Flemming, Adania; Phillips, Molly; Shea, Elizabeth K.; Bolton, Amy; Lincoln, Cynthia; Green, Kathryn; Mast, Austin; Cubeta, Marc A.
ABSTRACT: Natural history collections contain billions of specimens which are used to inform our understanding of the biodiversity of our planet. Digitized natural history collections (dNHCs) provide an accessible resource for multiple audiences, including K-12 teachers. The incorporation of dNHCs in K-12 classrooms provides an opportunity to engage students in authentic and practical science experiences. More importantly, through collaboration with museum educators the use of dNHCs can address some of the challenges K-12 teachers face when addressing the Next Generation Science Standards. Using primary data sources will ensure students understand the natural world through the perspective of scientific practices that involve data analyses, structured experiential and inquiry-based learning, and constructing explanations in a hypothesis-testing framework.